Motivasi Kerja Pegawai Pada Kantor Kelurahan Bone-Bone Kecamatan Bone-Bone Kabupaten Luwu Utara - Ardiansyah, Alif; Saputra, Sakral Wijaya; Latief, Mutmainnah; Muslimah, Utami Nur (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine what factors drive employee work motivation and efforts to improve employee work motivation at the Bone-Bone Village Office, Bone-Bone District, North Luwu Regency. The type of research uses a qualitative method with a descriptive research type. Data collection techniques through observation, interviews and documentation. The results of this study overall employee performance motivation at the Bone-Bone Village Office, Bone-Bone District, North Luwu Regency is not good using Abraham Maslow’s theory which consists of (1) physiological needs are met, there is rest time given for lunch, prayer and providing a drinking water dispenser; (2) The need for a sense of security is met, there is health insurance in the form of BPJS Employment; (3) Social needs are met, the work atmosphere is harmonious, comfortable, and full of familiarity, there is openness from superiors and participation of each employee through meetings; (4) The need for recognition of awards is met, giving praise, giving bonuses and sometimes recreation; (5) The need for self-actualization is quite met, there are special training activities for civil servants according to their competence.